Management and Outcomes of Non-A Non-B Aortic Dissection. (November 2022) - Liu, Jitao; Yang, Fan; Chen, Lyufan; Xie, Enmin; Su, Sheng; Liu, Yuan; Geng, Qingshan; Fan, Ruixin; Li, Jie; Luo, Jianfang
Abstract : Objective: The results of best medical treatment (BMT), endovascular based treatment (EBT), and total arch replacement (TAR) with frozen elephant trunk (FET) treatment in a single centre experience were reported in non-A non-B aortic dissection patients. Methods: From January 2016 to May 2020, 215 consecutive patients with acute or subacute non-A non-B aortic dissection were enrolled. The primary endpoints were all cause death. Secondary endpoints included follow up adverse aortic event (AE), a composite of the outcomes of dissection related death, rupture, retrograde type A aortic dissection, stent graft induced new entry tear, secondary endoleak, and follow up re-intervention. Kaplan–Meier curves were used to evaluate associations between different treatments and outcomes. Results: Among the 215 dissection patients, 127 (59.1%) received EBT, 42 (19.5%) received TAR + FET, and the remaining 46 (21.4%) received BMT. Thirty day mortality was higher in patients receiving TAR + FET (7.1%) than in those treated with EBT (1.6%) or BMT (2.2%) ( p = .12). However, after a median follow up of 39.1 (27.0 – 50.7) months, no additional death was recorded in the TAR + FET group, while nine (7.3%) patients died in the EBT group and 14 (31.8%) died in the BMT group ( p < .001). Specifically, EBT and TAR + FET showed no significant difference in midterm mortality rate, follow up AE, and re-intervention for complicated or uncomplicated dissection patients involving zone 2. For patients with uncomplicated non-A non-B aortic dissection involving zone 2, EBT could profoundly decrease the mortality rate, follow up AE and re-intervention when compared with BMT ( p < .010 for all), although this difference was not statistically significant between TAR + FET and BMT. No statistical comparison was performed in patients with zone 1 involvement because of the limited number of patients. Conclusion: It was demonstrated that EBT or TAR + FET might be a viable strategy for non-A non-B aortic dissection patients.